THE ROLE OF THE TEACHER IN EFL CLASSES - Ashurali , Mirzayev; Umirjonova , Shaxzoda; Xakimova , Zarafshon (Educational Research in Universal Sciences, 2023)
This article is useful for readers and teachers about several good ways in their studying and teaching process. It is about how to be a good supporter, motivator, well-organized teacher in EFL classes. Some roles of the teacher are defined. It includes how the EFL teacher give an effective lesson to learners and use some ways which are related to learning foreign languages.And also,some scientists’ opinions are given in this article.